2018
DOI: 10.1002/biot.201700669
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Local Flexibility Near the Active Site for Enzymatic Catalysis: Biochemical Characterization and Engineering of Cellulase Cel5A From Bacillus agaradherans

Abstract: Detailed molecular mechanisms underpinning enzymatic reactions are still a central problem in biochemistry. The need for active site flexibility to sustain catalytic activity constitutes a notion of wide acceptance, although its direct influence remains to be fully understood. With the aim of studying the relationship between structural dynamics and enzyme catalysis, the cellulase Cel5A from Bacillus agaradherans is used as a model for in silico comparative analysis with mesophilic and psychrophilic counterpar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Another target area is the catalytic site, the targeting non-catalytic amino acids achieved a 1.9-fold improvement in the catalytic efficiency in an endoglucanase [79]. In addition, loops and residues that may interact with the substrate have been widely studied [80][81][82][83]. As a semi-rational approach also focused on protein areas that interact with the substrate, strategies employed a complete diversity for selected positions.…”
Section: Engineering Cellulases For Enhanced Activity For Cellulose Dmentioning
confidence: 99%
“…Another target area is the catalytic site, the targeting non-catalytic amino acids achieved a 1.9-fold improvement in the catalytic efficiency in an endoglucanase [79]. In addition, loops and residues that may interact with the substrate have been widely studied [80][81][82][83]. As a semi-rational approach also focused on protein areas that interact with the substrate, strategies employed a complete diversity for selected positions.…”
Section: Engineering Cellulases For Enhanced Activity For Cellulose Dmentioning
confidence: 99%
“…Substitution of T83A and T45M led to an additional hydrogen bond between Tyr112 and Thr114 on β5 fold which located in substrate entrance tunnel. Hydrogen bond network is very important as it is reported that disrupting a hydrogen bond network in the vicinity of the active site increases local flexibility of cellulase Cel5A which led to increased catalytic activity at low temperatures but sharply declined catalytic activity at high temperature . Enhancement of β5 fold stability by new formed hydrogen bond could improve the thermostability of Bc LeuDH, because the ridigity of β5 fold was important for substrate entrance and also Asp117 on β5 fold is thought to be functioned during catalysis .…”
Section: Discussionmentioning
confidence: 99%
“…Three specific positions were selected based on the analysis of hydrogen bond patterns between residues within the active site. After sitedirected mutagenesis, Cel5A variants showed a concomitant increase in the catalytic activity at low temperatures and a decrease in activation energy and activation enthalpy, similar to cold-active enzymes, indicating that disrupting a hydrogen bond network in the vicinity of the active site increases local flexibility (Saavedra et al, 2018).…”
Section: Functionmentioning
confidence: 95%